Heart Failure with Preserved Left Ventricular Ejection Fraction in Patients with Acute Myocardial Infarction - Antonelli,Lucas (2015)
Abstract Background: The prevalence and clinical outcomes of heart failure with preserved left ventricular ejection fraction after acute myocardial infarction have not been well elucidated. Objective: To analyze the prevalence of heart failure with preserved left ventricular ejection fraction in acute myocardial infarction and its association with mortality. Methods: Patients with acute myocardial infarction (n = 1,474) were prospectively included. Patients without heart failure (Killip score = 1), with heart failure with preserved left ventricular ejection fraction (Killip score > 1 and left ventricle ejection fraction ≥ 50%), and with systolic dysfunction (Killip score > 1 and left ventricle ejection fraction < 50%) on admission were compared. The association between systolic dysfunction with preserved left ventricular ejection fraction and in-hospital mortality was tested in adjusted models. Results: Among the patients included, 1,256 (85.2%) were admitted without heart failure (72% men, 67 ± 15 years), 78 (5.3%) with heart failure with preserved left ventricular ejection fraction (59% men, 76 ± 14 years), and 140 (9.5%) with systolic dysfunction (69% men, 76 ± 14 years), with mortality rates of 4.3%, 17.9%, and 27.1%, respectively (p < 0.001). Logistic regression (adjusted for sex, age, troponin, diabetes, and body mass index) demonstrated that heart failure with preserved left ventricular ejection fraction (OR 2.91; 95% CI 1.35–6.27; p = 0.006) and systolic dysfunction (OR 5.38; 95% CI 3.10 to 9.32; p < 0.001) were associated with in-hospital mortality. Conclusion: One-third of patients with acute myocardial infarction admitted with heart failure had preserved left ventricular ejection fraction. Although this subgroup exhibited more favorable outcomes than those with systolic dysfunction, this condition presented a three-fold higher risk of death than the group without heart failure. Patients with acute myocardial infarction and heart failure with preserved left ventricular ejection fraction encounter elevated short-term risk and require special attention and monitoring during hospitalization.